Non-Hermitian photonics physics and application - Liu, Dongjue (Nanyang Technological University, 2023)
Non-Hermiticity significantly affects the physics of photonic systems, resulting in intriguing occurrences beyond the limits of Hermitian physics. For instance, the most widely studied non-Hermitian photonics systems with parity-time (PT) symmetry exhibit some important effects, including unidirectional invisibility, non-reciprocal wave propagation, loss-induced transparency, light stop, coherent absorber, etc. In this thesis, we investigate some new physics and applications based on non-Hermitian photonics systems, including the simultaneous manipulation of non-Hermitian line gaps and point gaps, the realization of non-Hermitian topological transition based on asymmetric backscattering, and the realization of perfect absorption in transformation optics-designed spatial Kramers–Kronig (KK) media.